2023
DOI: 10.14503/thij-23-8178
|View full text |Cite
|
Sign up to set email alerts
|

New Biomarkers for Cardiovascular Disease

Stephanie J. Kim,
Fernanda C. P. Mesquita,
Camila Hochman-Mendez

Abstract: Cardiovascular disease is the leading cause of death and disability worldwide. Early detection and treatment of cardiovascular disease are crucial for patient survival and long-term health. Despite advances in cardiovascular disease biomarkers, the prevalence of cardiovascular disease continues to increase worldwide as the global population ages. To address this problem, novel biomarkers that are more sensitive and specific to cardiovascular diseases must be developed and incorporated into clinical practice. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
0
4
0
1
Order By: Relevance
“…Extensive epidemiological research has identified a multitude of risk factors, which can be classified into modifiable and non-modifiable categories. Non-modifiable risk factors, including age, sex, genetics, and race, are beyond individuals' control ( 4 , 11 , 12 ). Of particular significance, age serves as an unmodifiable risk factor for CVDs, as the likelihood of developing CVDs escalate with advancing age ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive epidemiological research has identified a multitude of risk factors, which can be classified into modifiable and non-modifiable categories. Non-modifiable risk factors, including age, sex, genetics, and race, are beyond individuals' control ( 4 , 11 , 12 ). Of particular significance, age serves as an unmodifiable risk factor for CVDs, as the likelihood of developing CVDs escalate with advancing age ( 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…This study aims to compare the HCH model with the combined SMG model to comprehensively assess the strengths and weaknesses of different health management approaches. While the HCH model typically focuses on the continuity of care from healthcare institutions to homes and communities, the inclusion of SMG elements allows for further examination of the long-term impact of this model on patients' self-management abilities and health conditions ( 12 ). By conducting comparative research, differences among the models in patient engagement, health improvement outcomes, and healthcare resource utilization efficiency can be revealed, providing scientific evidence for policy-making and practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of people's living standard, cardiovascular disease has become a kind of disease threatening human health [1]. Studies have shown that the current incidence and mortality of cardiovascular diseases have exceeded malignant tumors, becoming the first incidence of disease [2]. More than 5 million people die of cardiovascular disease each year, and the age of onset is trending younger.…”
Section: Introductionmentioning
confidence: 99%
“…The genes, which exhibit varying degrees of activity under different circumstances, are examined to derive a functional profile of the group of genes. 15,16 In this study, we utilized networkanalyst.ca, a platform that employs limma to analyze the differential expression of genes in individuals with FH and atherosclerosis. Through analysis, we can identify the genes that have a key role in our specific ailment, offering a fresh perspective for diagnosis and study.…”
Section: Introductionmentioning
confidence: 99%